PENJADWALAN FLOWSHOP DENGAN MENGGUNAKAN SIMULATED ANNEALING - Muhammad Firdaus; Ilyas Masudin; Dana Marsetya Utama (Universitas Ahmad Dahlan Indonesia, 2015)
This article apply a machine scheduling technique, named Simulate Annealing (SA) to schedule 8 jobs and 5 machines to minimize makespan. A flowshop production flow is chosen as a case study to collect data and attempted to reduce jobs’ makespan. This article also does a sensitivity analysis to explore the implication of the changes of SA parameters as temperature. The results shows that the completion time of the jobs uses SA algoritm can decrease the completion time of the jobs, about 5 hours lower than the existing method. Moreover, total idle time of the machines is also reduced by 2.18 per cent using SA technique. Based on the sensitivity analysis, it indicates that there is a significant relationship between the changes of temperatures and makespan and computation time. Keywords : scheduling,simulated annealing, makespan flow shop.